Cover Feature: Challenges of Using Expansion Microscopy for Super‐resolved Imaging of Cellular Organelles (ChemBioChem 4/2021). (25th January 2021) - Büttner, Maximilian; Lagerholm, Christoffer B.; Waithe, Dominic; Galiani, Silvia; Schliebs, Wolfgang; Erdmann, Ralf; Eggeling, Christian; Reglinski, Katharina
Abstract : Seeing the hidden : In expansion microscopy (ExM) subcellular structures are imaged in isotropically expanded fixed samples, consequently allowing enlarged subcellular structures that would otherwise be hidden to standard microscopy to be resolved. Upon comparison of the expansion factors of different cellular compartments in cells within the same gel, we found significant differences in expansion factors of a factor of above 2. More information can be found in the full paper by K. Reglinski et al.